Evaluating the efficacy of the existing policy and framework for safeguarding women’s social rights in the prevention of domestic violence - Mohd Yusoff, Rahmawati; Sulistianingsih, Dewi; Ahmad, Nadzrah; Baharudin, Mohammad Hidir; Ismail, Noraini; Arshad, Azhani; Martitah, Martitah (The Brooklyn Research and Publishing Institute, 2024)
In recent times, a surge in domestic violence cases, has been observed in Malaysia. Consequently, a comprehensive understanding of current Malaysian and international policies/frameworks becomes imperative for safeguarding women’s social rights and preventing domestic violence. Employing qualitative research methods, including content analysis, this paper aims to identify the efficacy of the existing policy and framework based on Malaysian and International law for safeguarding women’s social rights in the prevention of domestic violence. The findings reveal that, despite numerous policies/frameworks established by international and Malaysian law to address domestic violence against women, instances continue to rise, and women persistently endure as victims. As a recommendation, it is proposed that the government enhances the efficacy of available mechanisms and frameworks, enabling women to realize their rights, responsibilities, and the protection afforded to them, ultimately addressing the issue of domestic violence in Malaysia.